2015
DOI: 10.1177/1479164114565631
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes and diastolic dysfunction on exercise capacity in normotensive patients without coronary artery disease

Abstract: Exercise capacity was found to be significantly decreased in normotensive patients with type 2 diabetes without coronary artery disease, and this decrease was independent of diastolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Similar VO 2 peak values compared to ours were found in a recent single centre study, with similar pre-and post-CR values and similar deficits of diabetic compared to non-diabetic patients [14]. The deficit in VO 2 peak found in our DM population was also reflected in lower VO 2 at the first ventilatory threshold and the VE/VCO 2 slope, consistent with what was documented previously [29,30]. Likewise, in our diabetic patients compared to those without DM, median peak heart rate was 4 bpm and 7 bpm lower at baseline and 12-month follow-up, respectively, and resting heart rate 2 bpm and 3 bpm higher, resulting in a 6 bpm and 10 bpm lower heart rate reserve, which may have, at least in part, accounted for the lower VO 2 peak.…”
Section: Vosupporting
confidence: 91%
“…Similar VO 2 peak values compared to ours were found in a recent single centre study, with similar pre-and post-CR values and similar deficits of diabetic compared to non-diabetic patients [14]. The deficit in VO 2 peak found in our DM population was also reflected in lower VO 2 at the first ventilatory threshold and the VE/VCO 2 slope, consistent with what was documented previously [29,30]. Likewise, in our diabetic patients compared to those without DM, median peak heart rate was 4 bpm and 7 bpm lower at baseline and 12-month follow-up, respectively, and resting heart rate 2 bpm and 3 bpm higher, resulting in a 6 bpm and 10 bpm lower heart rate reserve, which may have, at least in part, accounted for the lower VO 2 peak.…”
Section: Vosupporting
confidence: 91%
“…Our findings are consistent with those of aforementioned reports [14,15]. However, a more recent study by Gürdal et al reported that peak VO 2 in the maximum graded exercise test showed no statistically significant difference irrespective of the presence or absence of LV diastolic dysfunction in patients with type 2 diabetes and who had no apparent coronary artery disease [16]. Sacreet et al also reported that a 6-month exercise intervention successfully increased peak VO 2 by 11% in patients with type 2 diabetes.…”
Section: Subclinical Left Ventricular (Lv) Dysfunctionsupporting
confidence: 93%
“…Previous studies showed that reduced physical activity and oxygen consumption are associated with diabetes ( Gürdal et al., 2015 ). Accordingly, we found less movement and decreased oxygen consumption in HFD mice, whereas, mice treated with combination treatment showed increased activity and significantly increased oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%